Joint Statistics on Stereographic Projection of Contour Creating Algorithm Based on Regular Grid Data - Li Meng; Yao Guoqing; Cai Hongyue; Wang Haoyu; Ju Hengzhe (2014 Seventh International Symposium on Computational Intelligence and Design, 2014)
A joint is the structural trace generated by a certain part of crust by the action of tectonic stress in some epoch. The development law and characteristic of it extremely correlate with relevant structure in its area. Joint statistics plays an important role in structural analysis and engineering geological evaluation. Due to extensive data in actual measurement, heavy workload in traditional manual mapping and limited mapping precision of Wulff Net used in manual mapping process, manual mapping lacks precision and results in many errors. In recent years, there are a few researches involving realizing the function of storegraphic projection Joint statistics with the help of computers. We propose a method to realize the joint statistics on stereographic projection of contour creating algorithm based on regular grid data, through using statistical law of Pronin Net and inverse distance weighted grid interpolation algorithm, smooth handling of contour line by adopting B-Spline, contour line filled on the basis of topological relationship, so that stereographic projection net, joint point diagram, joint iso-intensity diagram and the filling of joint iso-intensity diagram can finally be drawn, and the accuracy of stereographic projection and preciseness of joint statistics can be improved dramatically.